Melt-under-cutting and buoyancy-driven calving from tidewater glaciers : new insights from discrete element and continuum model simulations - Benn, Douglas I.; Åström, Jan; Zwinger, Thomas; Todd, Joe; Nick, Faezeh M.; Cook, Susan; Hulton, Nicholas R. J.; Luckman, Adrian (Journal of Glaciology, 2017)
This work was funded by the ConocoPhillips Northern Area Program (CRIOS: Calving Rates and Impact on Sea Level) and the Nordic Research Council (SVALI: Stability and Variation of Arctic Land Ice and eSTICC: eScience Tools for Investigating Climate Change in northern high latitudes). The simple calving laws currently used in ice sheet models do not adequately reflect the complexity and diversity of calving processes. To be effective, calving laws must be grounded in a sound understanding of how calving actually works. Here, we develop a new strategy for formulating calving laws, using a) the Helsinki Discrete Element Model (HiDEM) to explicitly model fracture and calving processes, and b) the continuum model Elmer/Ice to identify critical stress states associated with HiDEM calving events. A range of observed calving processes emerges spontaneously from HiDEM in response to variations in ice-front buoyancy and the size of subaqueous undercuts. Calving driven by buoyancy and melt undercutting is under-predicted by existing calving laws, but we show that the location and magnitude of HiDEM calving events can be predicted in Elmer/Ice from characteristic stress patterns. Our results open the way to developing calving laws that properly reflect the diversity of calving processes, and provide a framework for a unified theory of the calving process continuum. Peer reviewed